A systematic review of brief mental health and well-being interventions in organizational settings - Ivana Ivandic; Aislinne Freeman; Ulrich Birner; Dennis Nowak; Carla Sabariego (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The aim of the systematic review was to provide an overview of the evidence on the effectiveness of brief interventions targeting mental health and well-being in organizational settings and compare their effects with corresponding interventions of common (ie, longer) duration. METHODS: An extensive systematic search was conducted using the Medline and PsycINFO databases for the period of 2000-2016. Randomized-controlled trials (RCT) and quasi-experimental studies evaluating primary or secondary brief interventions carried out in the workplace settings were included. Subsequently, common interventions matching brief interventions by type and assessed outcomes were included. The methodological quality of included studies was appraised using NICE guidelines and the best evidence synthesis approach was applied. RESULTS: The review identified 11 brief interventions and 9 corresponding common interventions. Included studies varied substantially in sample size and characteristics, methodological quality, duration of follow-up, types of intervention, and assessed outcomes. All but one study evaluating brief interventions had high risk of bias. No evidence was found on the effectiveness of brief stress management, relaxation, massage, mindfulness meditation, or multimodal interventions. We found limited evidence on the effectiveness of brief positive psychology interventions. CONCLUSIONS: Our review highlights the need for high-quality studies evaluating brief mental health and well-being interventions in organizational settings. Future studies should use methodologically rigorous designs and improved reporting of methods and results to provide conclusive evidence on the effectiveness and sustainability of the intervention effects.